Virtual Well-Being: Emotional and Behavioral Appraisal Patterns of an Immersive Experience - Photiadis, Thomas (sdf, 2017)
Virtual Worlds continue to promote improvements in real life, combining the visual appearance and the human behavior with each successive generation of hardware. Virtual environments are used with critical implications for business, education, social sciences and in the society at large. It is not an exaggeration to say that 3D spaces are treated as a parallel or alternative reality, cultivating and even shaping the individual’s personality. As a consequence, the evolution of virtual environments depends on individuals’ presence (interaction, behavior, attitude etc.), which is determined, partly, by the emotional elicitation. Emotional impact has a significant role in an immersive experience, in that it regulates and influences the in-world beings, hence producing the need for an in-depth investigation. However the impact of virtual experience on wellbeing remains unexplored (Riva et al., 2012). Limited evidence exists on the effectiveness of well-being in virtual environments (Gaggoli & Riva, 2013) which is complex and challenging task (Coyle et al., 2014).
Keywords: Emotions; Moods; Needs; Virtual Worlds; Human Behavior; User Experience; HCI; Media Psychology